2020
DOI: 10.1017/s1473550420000142
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the thermolysis of hydrogen cyanide: the role of hydrothermal systems in chemical evolution

Abstract: Abstract Hydrogen cyanide (HCN) is considered a fundamental molecule in prebiotic chemistry experiments due to the fact that it could have an important role as raw material to form more complex molecules, as well as it could be an intermediate molecule in chemical reactions. However, the primitive scenarios in which this molecule might be available have been widely discussed. Hydrothermal systems have been considered as abiotic reactors and ideal niches for chemical evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…These satellites present active hydrothermalism, and HCN might be produced in these extraterrestrial oceans, taking its easy formation under analogous terrestrial hydrothermal conditions into account 47 . The potential presence of HCN in these moons may lead to a complex organic chemistry 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…These satellites present active hydrothermalism, and HCN might be produced in these extraterrestrial oceans, taking its easy formation under analogous terrestrial hydrothermal conditions into account 47 . The potential presence of HCN in these moons may lead to a complex organic chemistry 51 , 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of minerals in HCN polymerization, previous reports have suggested that montmorillonite inhibits the formation of oligomers [ 47 , 56 ] and reduces the amount of carboxylic acids formed [ 58 ]. However, this does not mean that all mineral surfaces may have the same effect.…”
Section: Outlook On Studies About Prebiotic Molecular Complexitymentioning
confidence: 99%
“…Recent papers have shown that hydrothermal fluids, during the serpentinization process, can lead to the occurrence of carbonaceous matter on mineral surfaces [ 42 , 43 , 44 ]. In addition, it has been shown that alkaline conditions and the dynamic surroundings that are present in hydrothermal systems are crucial for the transformation of cyanide species (e.g., cyanide salts and hydrogen cyanide, HCN) into other organic precursors with interesting roles in pre-RNA world scenarios [ 11 , 12 , 45 , 46 , 47 , 48 ]. Therefore, it seems necessary to study the role of serpentinite during the polymerization of HCN in order to simulate a feasible primitive geochemical scenario such as the surroundings of an alkaline hydrothermal system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the interaction among minerals (olivine and orthopyroxene) with amino acids during several days (147 days) at 200 bar with periodic thermal cycling (30-100°C) leads to the synthesis of dipeptide species and their chemisorption (Takahagi et al, 2019). Other researchers have focused on the thermolysis and polymerization reactions of hydrogen cyanide under simple hydrothermal conditions (Das et al, 2019;Villafañe-Barajas et al, 2020a, 2020b and showed the formation of several organic compounds, suggesting that this kind of reactions could occur in the vicinity of hydrothermal vents. Moreover, other studies suggest that ferrocyanide solutions are stables at lower p CO 2 , temperature <25°C and higher pH (6.9-9.3); for example, in environments saturated in carbonate or bicarbonate brines (Toner and Catling, 2019).…”
Section: A Consistent Submarine Hydrothermal Vent Scenario?mentioning
confidence: 99%